MICROBIAL CONTAMINATION STANDARD OF CEMCEM LEAVES SAMPLE GROWN IN PEMOGAN VILLAGE, DENPASAR CITY - Rate, I Made Bagi; Sudimartini, Luh Made; Dharmayudha, Anak Agung Gde Oka (Buletin Veteriner Udayana; Vol. 15 No. 6 December 2023, 2023)
All parts of the cemcem plant ( Spondias pinnata (L.f.) Kurz) have been clinically tested to have various benefits in the health sector, making it ideal for processing into raw materials for herbal medicine. The high content of steroids, triterpenoids, phenolics and flavonoids in cemcem leaves has the potential to make cemcem leaves as natural antioxidants. The various phytochemical contents in cemcem leaves provide assorted properties so that they have the potential to produced and processed into numerous medicinal preparations. This study will calculate the number of microbes’ contamination in cemcem leaves that grow in Denpasar City. The examination of microbial contamination was carried out through the Total Plate Count (TPC) and Yeast Fungus Test (YFT). The research data obtained were quantitative data that were analyzed by counting the number of microbes that grow on PCA and PDA after incubation at the appropriate growth temperatures. The results of this study show that the Total Plate Count from the sample was 1,5 x  CFU/gram and the Yeast Fungus Test was 3,5 x  CFU/gram. So the results of these studies can be concluded the number of ALT has fulfilled the requirements for the Semi Solid Drugs (colony/gram) but do not qualify the requirements for the Oral Drugs (colony/gram) on the number of AKK are required for Semi Solid Drugs (colony/gram) but do not qualify the requirements for the Oral Drugs (colony/gram). So it can be concluded that samples of cemcem leaves that grow in Pemogan Village, Denpasar City can only be processed into external raw medicine. It is necessary to apply Good Traditional Medicine Manufacturing Methods to obtain quality products and to re-sterilize simplicia samples using UV radiation and gamma rays to reduce the amount of microbial contamination.